The Significance of Maslahah as a Legal Consideration in Family Inheritance - Mujab, Sayful; Rahma, Nabila Luthvita (Universitas Islam Sultan Agung, 2025)
This study aims to examine the significance of maslahah (benefit) as a legal consideration in family inheritance, with a specific focus on the principal issue of how the practices of division and transfer of family inheritance occur in Margoyoso Village, Kalinyamatan District, Jepara Regency, and the relevance of the principle of maslahah as a foundational legal consideration. In alignment with the focus of the problem, this study is classified as field research employing a qualitative approach based on case studies. Data were collected through in-depth interviews using a semi-structured method with eight informants, comprising heirs, religious and community leaders, notaries, and advocates. The findings of the study suggest that the transfer of inheritance rights within the distribution of family inheritance in Margoyoso Village, Kalinyamatan District, Jepara Regency, reflects values of social justice and humanity. The transfer of inheritance rights, conceptualised as a gift from an Islamic legal perspective, indicates alignment with the principle of maslahah. However, the findings also reveal weaknesses in the formal legal aspect, particularly when viewed through the lens of the Indonesian Civil Code, as the process of transferring inheritance rights is predominantly conducted through verbal agreements, which may potentially lead to future conflicts. This study advocates for the development of discourse on the integration of Islamic law and positive law, specifically concerning the transfer of inheritance rights within the distribution of family inheritance. Furthermore, it aims to serve as a reference for the government in formulating legal policies that emphasise the integration of maslahah theory in Islamic law with benefit theory in positive law, in order to uphold justice, legal certainty, and the continuity of family relationships.